التراضي كاستثناء لإبرام الصفقات العمومية بين التقييد والحرية - منيـــــــــــــــرة مغني (جامعة محمد بوضياف المسيلة, 2019)
حرصا منه على حماية المال العام اعتبر المشرع طلب العروض القاعدة العامة في إبرام الصفقات العمومية، وهي الصيغة الأكثر تنافسية لاعتمادها على طابع الشكلية في كل الإجراءات، في المقابل وتأكيدا على هذا الحرص مكن المصلحة المتعاقدة من اللجوء استثناءً إلى التراضي لإبرام صفقة عمومية وقيدها في ذلك بحالات وظروف وإجراءات معينة، هذه الشروط جاءت لتحقيق المقصد الرئيسي من هذا الاستثناء والمتمثل في تسهيل عمل المصلحة المتعاقدة بتجنيبها طول الإجراءات وتعقيدها وتحقيق الانجاز في أسرع وقت، هذه الصيغة في الإبرام أوجد لها المشرع هي الأخرى الآليات الكفيلة بتحقيق المقاربة بين تخفيف الإجراءات والوقاية من الفساد، وقد جاءت هذه الدراسة للوقوف على الضمانات التي كفلها المشرع في تأطيره للتراضي بشكليه وبيان كيف استفاد المشرع من الثغرات القانونية التي حملتها التنظيمات السابقة في التحسين من تأطير هذه الصيغة في إبرام الصفقات العمومية في المرسوم الرئاسي 15-247. Abstract: Key words : public deal, compromise, simple compromise, compromise after the consultation. In order to protect the public money, the legislator had considered the calls of tenders as a general rule for the execution of public deals, it is the most competitive format as it takes the formalism shape in all its procedures, and in return to confirm this car signed party contracting made acces to the rapprochment so that to make a pblic deal, the latter is restricted by certain circumastances and procedures, thes conditions came to realize the main purpose which is facilitating the job og the signed prty by reducing the long procedures and their complexity and also to achieve the targeted project fastly, this format in making a bargain, the legislator had found new techniques to achieve it between reducing the procedures and preventing corruption, this study came to bring guaranties which the legislator had ensuredin framing the rapprochement and to clarify how the legislator got benefits from the breaches of the law which the previous systems had mad in improving the format framing in making the public deals, in the presidentiel decre
Keywords: : public deal, compromise, simple compromise, compromise after the consultation.; الصفقات العمومية، التراضي، التراضي البسيط، التراضي بعد الاستشارة